IMPLEMENTATION OF DATA ENCRYPTION IN AN IOT-BASED HEART RATE AND OXYGEN SATURATION BLOOD DETECTION TOOL USING THE ELGAMAL METHOD - Haryansyah, Haryansyah (Jurnal Teknik Informatika (Jutif), 2024)
One of the problems with Internet of Things (IoT) devices today is data security. Especially regarding IoT devices that function to read personal or confidential data such as health-related data. This research focuses on discussing data security techniques through the process of encrypting sensor data that reads heart rate and blood oxygen saturation from an IoT device. This data is quite personal and confidential data because it concerns a person's medical history. The encryption method that will be used is the Elgamal method. The Elgamal method is an asymmetric encryption method, meaning the key used for encryption is different from the key used for decryption. This elgamal method uses a public key for encryption and a private key for decryption. The research results show that implementing data encryption using the Elgamal method to secure data on IoT devices was successful. Data security can prevent misuse of data by unauthorized parties.